Survival analysis of transplant-eligible newly-diagnosed multiple myeloma patients harboring t(4;14), t(14;16), and/or del(17p) in the real-world setting - Garrido, David; Slavutsky, Irma; Riva, Eloisa; Peña, Camila; Schutz, Natalia; Tarín-Arzaga, Luz; Martínez-Cordero, Humberto; Bove, Virginia; Osorio, Rocío; Chandía, Mauricio; Beltrán, Cecilia; Schulz, Javier; et al. (Current problems in cancer, 2023)
Cytogenetic abnormalities (CA) such as t(4;14), t(14;16), and del(17p), are associated with a poor prognosis in Multiple Myeloma (MM) patients. However, there is scarce information regarding the Latin-American population. This study aims to analyze the impact of t(4;14), t(14;16), and del(17p) on the progression-free survival (PFS) and overall survival (OS) of transplant-eligible newly-diagnosed MM (NDMM) patients in Latin America. Retrospective survival analysis based on the Grupo de Estudio Latinoamericano de MM (GELAMM) registry, including all adult patients with NDMM harboring CA t(4;14), t(14;16), and/or del(17p). Fifty-nine patients were included; the median age was 57 years, 55.9% males, 22% ISS-I, 25.4% ISS-II, and 47.5% ISS-III. The majority (89.8%) had one alteration, whereas 10.2% had del(17p) and t(4;14). The frequencies of CA were del(17p) in 61.0%, t(4;14) in 25.4%, and t(14;16) in 3,4%. Autologous stem cell transplantation was performed in 36 cases, 20 patients did not use this consolidative strategy, and this data was missed in three cases. Five-year OS for the entire cohort was 60.8% and 5-year PFS was 28.1%. Bortezomib-based induction regimen (BBR) (p=0.029), consolidation with ASCT (p<0.001), and maintenance therapy (p=0.004) were associated with an improved 5-year OS. In the multivariate analysis, ASCT was the only variable with a positive impact on OS (HR 0.11, 95% CI 0.033 to 0.34, p<0.001). The median PFS presented a non-statistically significant benefit in BBR, ASCT, and maintenance therapy groups. BBR induction, ASCT, and maintenance therapy were associated with improved OS in high-risk NDMM patients.